2015
DOI: 10.1007/s10517-015-3074-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-4, Interleukin-10, and Tumor Necrosis Factor-α Polymorphic Genes in the Pathogenesis of Occupational Allergic Dermatoses

Abstract: Study of polymorphic genes of pro- and anti-inflammatory cytokines (IL-4, IL-10, TNF-α) in patients with occupational allergic dermatoses showed significantly higher frequency of polymorphic variants of cytokine genes IL4 C589T, IL10 C819T, IL10 G1082A, IL10 C592A, and TNF G308A in comparison with the population control. The presence of homozygous variant IL10 G1082A--AA in 80% cases characterizes early disease development, i.e. within 3 years after the first exposure to the occupational factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
5
Order By: Relevance
“…A similar association has been reported with occupational allergic dermatoses in Russian patients. 35 However, GA genotype of TNF-α (308 G/A) is significantly decreased and the frequency of GG genotype is increased in the patients showing a negative association of this polymorphism with AD and atopic asthma in Iranian 23 and Croatian patients. 36 On the contrary, some studies have indicated no association of TNF-α (308 G/A) polymorphism with AD susceptibility in English, 37 German, 20 Americans.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A similar association has been reported with occupational allergic dermatoses in Russian patients. 35 However, GA genotype of TNF-α (308 G/A) is significantly decreased and the frequency of GG genotype is increased in the patients showing a negative association of this polymorphism with AD and atopic asthma in Iranian 23 and Croatian patients. 36 On the contrary, some studies have indicated no association of TNF-α (308 G/A) polymorphism with AD susceptibility in English, 37 German, 20 Americans.…”
Section: Discussionmentioning
confidence: 96%
“…63 Contrarily, −819 C/T, and −592 A/C have been reported to be significantly associated with AD in Czech 22 and Korean population, 28 with increased allergies and risk for persistent late-onset wheezing in young Finish children 60 and with occupational allergic dermatoses in Russian patients. 35 AD has been defined as a biphasic disease including an initial phase predominated by T helper type 2 (Th2) cytokines and later more chronic Th1-dominated eczematous phase. 9,65 Lymphocytes T(H)2-type only are activated in acute form of AD whereas lymphocytes of both T(H)1-and T(H)2-type are dominated in more chronic forms of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ІЛ-10 є протизапальним цитокіном, який продукується T-хелперами-2 (Th2), В-лімфоцитами, макрофагами, кератиноцитами, тучними клітинами, тимоцитами. ІЛ-10 є інгібітором запалення й інгібує синтез цитокинів Т-хелперами-1 (Th1), тим самим регулюючи баланс Th1/Th2 (пригнічується клітинна відповідь і підсилюється гуморальна) [10].…”
Section: вступunclassified
“…Так, вивчався вплив поліморфізму гена ІЛ-10 G1082A на перебіг позалікарняної пневмонії. Під час дослідження науковці визначили, що він знаходиться в переліку тих генів, мутації яких найчастіше зустрічаються у Існують наукові дослідження, що вказують на зв'язок мутації гена ІЛ-10 з розвитком професійних алергічних дерматозів [10]. Інші автори повідомляють, що під час дослідження не виявлено вірогідних зв'язків між перебігом астми, атопічним дерматитом і поліморфізмом G1082A гена ІЛ-10 [15].…”
Section: обговоренняunclassified